If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + -2(x + 1) = 0 Reorder the terms: 3(-3 + x) + -2(x + 1) = 0 (-3 * 3 + x * 3) + -2(x + 1) = 0 (-9 + 3x) + -2(x + 1) = 0 Reorder the terms: -9 + 3x + -2(1 + x) = 0 -9 + 3x + (1 * -2 + x * -2) = 0 -9 + 3x + (-2 + -2x) = 0 Reorder the terms: -9 + -2 + 3x + -2x = 0 Combine like terms: -9 + -2 = -11 -11 + 3x + -2x = 0 Combine like terms: 3x + -2x = 1x -11 + 1x = 0 Solving -11 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 1x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 1x = 0 + 11 1x = 0 + 11 Combine like terms: 0 + 11 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 96t-16t^2-80=0 | | 5x+5=-115 | | 4+5x+9=7x-1 | | 4x^2-7x+11=9x+4 | | 0.75m+3=9 | | 2x-4(3-x)=7x+5 | | 5a-(2-a)=2a-14 | | 32t+-12=3t+42 | | 4[a+3]=2a+62 | | 24513465134+134613461= | | 19+t=-133 | | -14=w+3 | | 7z+14=5z+29 | | 18n=13 | | H=90-5t^2 | | 12=-4t | | 4+5x+9=7x+1 | | 8x+2=-6+3x+23 | | x^4+2x^2-36=0 | | (4x+5y)+(x+7y)= | | 1.5-0.04x=1.5 | | (x^2)-(2x)+(2)=0 | | 8+2=-6+3x+23 | | 5x+11y=-13 | | 7(v+3)-4v=27 | | 3x-9=12x-13 | | (X^2)-216=0 | | x^2-8x-42=-2x-2 | | -60p+260=90p-40 | | X(-2)=-64 | | s+0.25s+20=55 | | -5p^2+15000p-1750000=0 |